The Contribution of Self Regulated Learning to Students’ Active Participation in PAI Learning at SMP Negeri 3 Bukittinggi - Tika Musliha; Fenny Ayu Monia (Lembaga Yasin AlSys, 2026)
Self-regulated learning has received considerable attention in educational research, but studies examining its contribution to students’ learning engagement in Islamic Religious Education (PAI) at the junior secondary school level, particularly at SMP Negeri 3 Bukittinggi, remain limited. This study aimed to analyze the levels of self-regulated learning and learning engagement and the contribution of self-regulated learning to students’ learning engagement in PAI at SMP Negeri 3 Bukittinggi. This study employed a quantitative approach with a causal-comparative design. The sample comprised 135 Grade VII students selected through proportional random sampling. Data were collected using a questionnaire and subsequently analyzed through descriptive statistics, Pearson product–moment correlation, and simple linear regression with the assistance of SPSS Statistics version 25. The results showed that self-regulated learning was in the moderate category, encompassing 83.70% of the students, while learning engagement was also in the moderate category, encompassing 88.89% of the students. The regression analysis yielded a correlation coefficient (R) of 0.892 and a coefficient of determination (R²) of 0.795. These results indicated that self-regulated learning was strongly associated with learning engagement and explained 79.5% of the variation in students’ learning engagement within the research model, while the remaining 20.5% was associated with other factors outside the model. These findings provide empirical evidence of the role of self-regulated learning in supporting student engagement in PAI. This study highlights the need for PAI teachers and schools to develop students’ self-regulation by fostering the habitual planning, monitoring, reflection, and evaluation of the learning process.